2011
DOI: 10.3389/fpsyg.2011.00197
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implicit Hand-Based Representations on Mental Arithmetic

Abstract: Recently, a strong functional relationship between finger counting and number processing has been suggested. It has been argued that bodily experiences such as finger counting may influence the structure of the basic mental representations of numbers even in adults. However, to date it remains unclear whether the structure of finger counting systems also influences educated adults’ performance in mental arithmetic. In the present study, we pursued this question by examining finger-based sub-base-five effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 43 publications
5
61
0
1
Order By: Relevance
“…Vinod Menon, a developmental cognitive neuroscientist at Stanford University in California, and his colleagues presented single-digit addition problems to 28 children aged 7-9, as well as to 20 adolescents aged 14-17 and 20 young adults. Consistent with previous psychology studies, the children relied heavily on counting out the sums, whereas adolescents and adults tended to draw on memorized information to calculate the answers (Klein et al, 2011).…”
Section: Introductionsupporting
confidence: 50%
“…Vinod Menon, a developmental cognitive neuroscientist at Stanford University in California, and his colleagues presented single-digit addition problems to 28 children aged 7-9, as well as to 20 adolescents aged 14-17 and 20 young adults. Consistent with previous psychology studies, the children relied heavily on counting out the sums, whereas adolescents and adults tended to draw on memorized information to calculate the answers (Klein et al, 2011).…”
Section: Introductionsupporting
confidence: 50%
“…Multiple studies have shown that finger counting habits influence number processing performance (Domahs et al 2010;Newman and Soylu 2014) and interact with visuospatial representations of numbers (Fischer 2008). Furthermore, there is evidence for adults' unconscious encoding of small numbers in the form of finger numeral representations (Badets et al 2010) and finger counting patterns affecting arithmetic performance based on a sub-base-five effect (Klein et al 2011). In multiple studies, it has been shown that finger sense (Fayol et al 1998;Noel 2005) and fine motor ability (Luo et al 2007) predict mathematical performance in young children.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, in a large cohort of primary schoolers, calculation errors frequently include the erratic assignment of full hands (i.e., 5 items; Domahs, Krinzinger, & Willmes, 2008). But also in adults, implicit hand-based magnitude representations were reported to produce increased calculation latencies when addition problems crossed the five-boundary (Klein, Moeller, Willmes, Nuerk, & Domahs, 2011). In Western groups, such sub-base-five effects had been particularly pronounced and it was concluded that finger experiences (i.e., counting habits) influence mental number representations (Domahs, Moeller, Huber, Willmes, & Nuerk, 2010).…”
Section: Different Shapes Of Categorical and Linear Spatial Mappingsmentioning
confidence: 99%